2018
DOI: 10.1002/elps.201800007
|View full text |Cite
|
Sign up to set email alerts
|

Determination of 16 antineoplastic drugs by capillary electrophoresis with UV detection: Applications in quality control

Abstract: Two capillary electrophoresis (CE) methods were developed for the analysis of 16 antineoplastic drugs contained in injectable pharmaceutical formulations. A capillary zone electrophoresis (CZE) method coupled to UV was developed with a background electrolyte (BGE) made of a 100 mM phosphate buffer at pH 2.5 containing 50% v/v of acetonitrile and dynamic coating of capillaries with Ceofix®. This method allowed the analysis of doxorubicin, epirubicin, idarubicin, daunorubicin, irinotecan, topotecan, vincristine,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…CE using low amount of sample, cheap capillaries, high speed, and high resolution and efficiency has been proposed as another technique to separate MTX in different matrices, by Castro-Puyana et al., Cheng et al., and Guichard et al. [[115], [116], [117], [118]]. Due to the importance of cerebrospinal fluid (CSF) during chemotherapy and relapse, the evaluation of MTX and its metabolites in CSF was performed by triple-stacking CE [116].…”
Section: Capillary Electrophoresis (Ce)mentioning
confidence: 99%
“…CE using low amount of sample, cheap capillaries, high speed, and high resolution and efficiency has been proposed as another technique to separate MTX in different matrices, by Castro-Puyana et al., Cheng et al., and Guichard et al. [[115], [116], [117], [118]]. Due to the importance of cerebrospinal fluid (CSF) during chemotherapy and relapse, the evaluation of MTX and its metabolites in CSF was performed by triple-stacking CE [116].…”
Section: Capillary Electrophoresis (Ce)mentioning
confidence: 99%
“…The rapid body clearance, large distribution volume, and low plasma concentration of vinblastine necessitate a rapid, sensitive, and selective analytical method to achieve reliable pharmacokinetic studies. 13,14 Different methods have been reported in the literature for the determination of vinblastine including spectrophotometry, 15,16 thin layer chromatography, 17 high-performance liquid chromatography, [18][19][20][21][22][23][24][25][26] capillary electrophoresis, [27][28][29][30][31] and voltammetric methods. [32][33][34][35][36][37] As far as the authors' knowledge, no potentiometric sensor is reported in the literature for the determination of vinblastine.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, developing a simple, rapid and highly sensitive method for MTX detection has received increasing attention. Recently, high‐performance liquid chromatography (HPLC) , capillary electrophoresis (CE) and fluorescence spectroscopy techniques were widely used as high accuracy techniques for monitoring of MTX in real samples. But, HPLC and CE are expensive instruments; also using fluorescence spectroscopy process needs complicated sample preparation processes, which limited their clinical applications.…”
Section: Introductionmentioning
confidence: 99%